The effect of tempo and register modulation on sustained and selective auditory attention in a musical target detection task - Stevens, Christine K., author; Thaut, Michael H., advisor; Davis, William B., committee member; Baez, Victor A., committee member (Colorado State University. Libraries, 1998)
This study investigated performance on a musical target detection task under four conditions in which the tempo was either fast (120 bpm) or slow (80 bpm), and the target was either in the upper register or lower register (1 octave lower). A target detection task was utilized to examine sustained and selective auditory attention. Performance measures included number of correct targets detected, number of commission errors, and response time in milliseconds. Jones' (1992) theory of rhythmic attending predicts that an entrainment effect occurs at the referent level (musical measure) of attending to the musical stimulus. Sloboda's (1985) hypothesis of attention and music predicts that performance in the upper register conditions should be superior to the lower register conditions. These predictions were examined through a target detection task, modeled upon similar visual attention studies. The author composed music which embedded a three note target regularly occurring at an interpresentation interval (IPI) of four measures. The target occurred a total of twenty four times in each condition. Nineteen non-musician subjects from the Social Work undergraduate classes participated in the experiment. All subjects heard the four conditions with the tempo conditions counter-balanced. The higher register conditions always preceded the lower register conditions due to anticipated higher level of difficulty for lower register or more hidden target conditions. Results indicated no significant effects of tempo or register when performance was analyzed by condition, an indication of selective attention. The use of time segmentation of performance data was then analyzed to examined sustained attention. Again, there was no significant effect of tempo and register modulation upon performance over time. This result indicates that subjects were able to sustain their attention. Indeed, a visual analysis of the results of target accuracy revealed that subjects sustained a generally high level of performance (68%) across all conditions. Responses to an open-ended question regarding what strategy subjects used were analyzed qualitatively. An ANOV A demonstrated that strategy did demonstrate a significant effect on response time (p = .049). A post-hoc analysis indicated that subjects who used the anticipation/timing strategy were significantly faster in their responses than those who used the repetition strategy (p = .016). These results support the primacy of timing within auditory attentional processing (Marks and Crowder, 1997, Jones, 1992). Furthermore, a cognitive timing mechanism is discussed. Music facilitated attending and attentional distraction models in clinical music therapy are discussed.
Keywords: Auditory perception; Music therapy